2013
DOI: 10.1093/ejcts/ezt103
|View full text |Cite
|
Sign up to set email alerts
|

The role of Willis circle variations during unilateral selective cerebral perfusion: a study of 500 circles†

Abstract: Our results show that CW variations are present in a significant number of patients. Our data support the need for extensive preoperative examination and meticulous intraoperative monitoring of cerebral perfusion during uSCP. Finally, our data support the superiority of bilateral SCP over uSCP, because most of the variations reported do not have haemodynamic significance during bilateral SCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 15 publications
0
51
0
1
Order By: Relevance
“…The general target was 28 C, with the lower range temperatures representing extra caution exercised early in our experience or in patients in whom distal circulatory arrest was needed. Individual arch branch clamp times were 14 (10-18) minutes for the innominate artery, 11 (9)(10)(11)(12)(13)(14) minutes for the left carotid artery, and 18 (13-23) minutes for the subclavian artery reconstruction. Left subclavian artery reconstruction was longer because of its deeper position and a lower perceived urgency in the need to reperfuse it (Table 3).…”
Section: Perfusion Datamentioning
confidence: 99%
“…The general target was 28 C, with the lower range temperatures representing extra caution exercised early in our experience or in patients in whom distal circulatory arrest was needed. Individual arch branch clamp times were 14 (10-18) minutes for the innominate artery, 11 (9)(10)(11)(12)(13)(14) minutes for the left carotid artery, and 18 (13-23) minutes for the subclavian artery reconstruction. Left subclavian artery reconstruction was longer because of its deeper position and a lower perceived urgency in the need to reperfuse it (Table 3).…”
Section: Perfusion Datamentioning
confidence: 99%
“…However, controversies still exist regarding unilateral brain perfusion, bilateral perfusion, or triple perfusion because most of the clinical studies have mixed up patients who had hemiarch replacement and total arch replacement [21]. Anatomical studies have revealed that 20-30 % of normal individuals had at least one paucity of the circle of Willis in brain circulation [22].…”
Section: Brain Protectionmentioning
confidence: 99%
“…Even in elective proximal arch surgeries, a 6% rate of paraplegia is encountered, highlighting the need for further measures to reduce this devastating complication, especially in the case of more time demanding extensive aortic repairs 21 . In this context, additional perfusion of LSA seems to be beneficial, particularly in critical vascular conditions, such as concomitant carotid dissections, acute right vertebral artery occlusion, dominant LVA, or inadequate intracranial arterial communications 22–27 . Notably, studies reporting on outcomes after thoracic endovascular aortic repair with overstenting of the LSA have demonstrated an increased risk of left‐hemispheric stroke and permanent paraplegia 28–30 .…”
Section: Resultsmentioning
confidence: 99%